MEN AUDITOR, WOMEN AUDITOR AND AUDIT QUALITY - ASTRID RUDYANTO; IRWANTO HANDOJO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
Many researches on auditor specific characteristic use evidence from psychological researches on the existence of certain sex-based differences amongst individuals.The objective of this study is to see whether indeed there are sex differences in auditor interms of risk profile, problem solving skill, and independence - three important traits with potential of influencing the auditor judgment and audit quality-as it is not obvious thatstereotypical believes about men and women are true or that findings from literature aboutthe general population can be interpreted to the specific context of auditors. Primary data was employed for the study using a sample of 115 auditors, 175 accounting students, 112 management students and 114 nonaccounting and nonmanagement students with independent sample test and mann-whitney u test. The findings suggested there is no sex difference in auditors while overall, there is sex difference in risk profile. It is concluded that there is no sex difference affecting audit quality.